Design Thinking for Social Innovation in Health Care : a local perspective, the City of Dundee, Scotland / Louise Valentine, Thilo Kroll, Fraser Bruce, Chris Lim and Rodney Mountain - Valentine, Louise
Health Equality is a social and behavioural problem as well as a medical one, and it constitutes one of the most pressing challenges worldwide. If we take the City of Dundee as an example, and look at a recent report on the situation of people who are at risk of homelessness, in the city (Fernandes and Sharp, 2015), the key issues identified by people exposed to this potential reality were ‘money/benefits’ (78%) followed by ‘unemployment’ (68%) and ‘food’ (60%). The immediate context of the City of Dundee’s wellbeing is important and will be touched upon, however, in this paper we focus on future scenarios, especially how the infrastructures for tomorrow’s health and social care issues can be considered today. We know in the UK, it is estimated there will be more than 8 million people over the age of 80 living in our cities by 2050 (Cracknell, 2010). Given the direct link between education and health and, the natural deterioration and the increased occurrence of ill health as people grow older, with greater occurrences of cancer, dementia and hip replacements for example, there is an exigency to rethink normal ways of working. Three projects will be discussed. The first looks at the design of a new method to facilitate entrepreneurship, and nurture a relation between social innovation, design thinking and healthcare. It brings together the sprint method – a process to inculcate radical change - with the theory and practice of design thinking, to hold participants in an iterative phase of learning and development. With a focus on design for social innovation in healthcare (e.g. breast cancer, anxiety, depression) we will share how this agile way of working demonstrates a new strategy for pedagogy, one which champions partnership and unites different educational communities with their associated industry links. The second case study ‘Healthcare Designed in Dundee’ discusses design as a strategy for social transformation, developing an understanding of the potential value of service design in supporting health and social care infrastructure and ecosystems. The premise of both studies is that if design is innovation and innovation is design, it is not ill conceived to consider what, how and where design can strategically help solve the social and behavioural problem that is Health Equality. Finally, the third case study will reflect on the challenges and opportunities encountered when developing our pedagogic theory and practical approaches for integrating health and social issues into the design curriculum. Paying particular attention to how technology has been used to build working prototypes to test and share ideas, the case study will draw upon the personal experience of teaching staff in relation to the following student work: Pulse, a wrist worn device designed specifically to tackle mild depression through exercise. One Heart, an intimate toolkit aimed at encouraging personal engagement and responsibility in hypertension treatment. Unfold, a personal toolkit designed for family members with caring responsibilities for those with dementia.